Effects of environmental temperature on growth performance, muscle fiber structure, fatty acid composition, and gene expression in ducks - Ziyi Pan; Congcong Xu; Dongyue Sun; Xingda Yang; Rihong Guo; Zichun Dai; Fang Chen; Zhendan Shi; Shijia Ying (Poultry Science)
This study aims to elucidate the effects of environmental temperature on growth performance, pectoral muscle fiber structure, fatty acid composition, and gene expression in ducks. A total of 72 ducks at 21-day-old were randomly assigned to controlled environments at temperatures of 20°C (T20) and 29°C (T29) from 21 to 42 days of age. Ducks in the T20 group exhibited significantly higher body weight, body weight gain (BWG), average daily gain (ADG), and average daily feed intake (ADFI) at 42-day-old compared to those in the T29 group (P < 0.05). T20 group showed a marked reduction in muscle fiber diameter and area, with an increase in fiber density compared to those raised at T29 group (P < 0.05). The T20 group also had higher levels of various fatty acids, including saturated (SFAs), monounsaturated (MUFAs), and polyunsaturated (PUFAs) types, while T29 group had lower levels of ω-3 and ω-6 PUFAs and a higher ω-6/ω-3 PUFA (P < 0.05). Transcriptomic analysis revealed 544 differentially expressed genes (DEGs) primarily associated with the Cell Cycle, Cell Replication, and PPAR signaling pathways, with key genes cell division cycle 45 (CDC45), chromatin licensing and DNA replication factor 1 (CDT1), and others identified through protein-protein interaction (PPI) network analysis as crucial for temperature regulation of muscle fiber structure and fatty acid composition, particularly within the significantly enriched cell cycle pathway. These findings were validated by qPCR, confirming consistent gene expression trends. The study highlights how ambient temperature affects muscle fiber characteristics and fatty acid composition in ducks, offering insights into potential strategies for optimizing production conditions to enhance meat quality and efficiency.